In vivo requirements for GATA-1 functional domains during primitive and definitive erythropoiesis - Shimizu, Ritsuko (Oxford University Press, 2001)
GATA-1 is a transcription factor essential for erythroid/megakaryocytic cell differentiation. To investigate the contribution of individual domains of GATA-1 to its activity, transgenic mice expressing either an N-terminus, or an N- or C-terminal zinc finger deletion of GATA-1 (ΔNT, ΔNF or ΔCF, respectively) were generated and crossed to GATA-1 germline mutant (GATA-1.05) mice. Since the GATA-1 gene is located on the X-chromosome, male GATA-1 mutants die by embryonic day 12.5. Both ΔNF and ΔCF transgenes failed to rescue the GATA-1.05/Y pups. However, transgenic mice expressing ΔNT, but not the ΔNF protein, were able to rescue definitive hematopoiesis. In embryos, while neither the ΔCF protein nor a mutant missing both N-terminal domains (ΔNTNF) was able to support primitive erythropoiesis, the two independent ΔNT and ΔNF mutants could support primitive erythropoiesis. Thus, lineage-specific transgenic rescue of the GATA-1 mutant mouse revealed novel properties that are conferred by specific domains of GATA-1 during primitive and definitive erythropoiesis, and demonstrate that the NT and NF moieties lend complementary, but distinguishable properties to the function of GATA-1.